1999
DOI: 10.1063/1.873617
|View full text |Cite
|
Sign up to set email alerts
|

Radiative properties of high wire number tungsten arrays with implosion times up to 250 ns

Abstract: High wire number, 25-mm diameter tungsten wire arrays have been imploded on the 8-MA Saturn generator, operating i n a long-pulse mode. By varying the mass load from 710 to 6140 ug/cm, implosion times of 130 to 250 ns have been obtained with implosion velocities of 50 to 25 c d p s , respectively. z-pinch implosions produced plasmas with millimeter diameters that radiated 600 to 800 kJ of x-rays, with powers of 20 to 49 TW; the c&esponding pulsewidths were 19 to 7.5 ns, with risetimes ranging from 6.5 to 4.0 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Recent timeresolved iron spectra at Sandia confirm an ion temperature T i of over 200 keV (2 10 9 degrees), as predicted by theory. These are believed to be record temperatures for a magnetically confined plasma.There has been some difficulty in understanding how the radiated energy in a wire-array Z pinch implosion could be up to 4 times the kinetic energy [1][2][3][4], and also how the plasma pressure could be sufficient to balance the magnetic pressure at stagnation if the ion and electron temperatures were equal. In fact, theoretically the excess magnetic pressure should continue to compress the plasma leading to a radiative collapse.…”
mentioning
confidence: 99%
“…Recent timeresolved iron spectra at Sandia confirm an ion temperature T i of over 200 keV (2 10 9 degrees), as predicted by theory. These are believed to be record temperatures for a magnetically confined plasma.There has been some difficulty in understanding how the radiated energy in a wire-array Z pinch implosion could be up to 4 times the kinetic energy [1][2][3][4], and also how the plasma pressure could be sufficient to balance the magnetic pressure at stagnation if the ion and electron temperatures were equal. In fact, theoretically the excess magnetic pressure should continue to compress the plasma leading to a radiative collapse.…”
mentioning
confidence: 99%
“…The rise time is a good metric of the implosion quality, since in Ref. 14 it was noted that the pinch reached minimum compression at the time of peak power; thereafter on-axis MHD instabilities ͑mϭ0 and mϭ1͒ were observed. This along with analyses of two-dimensional MHD calculations by Peterson et al 24 would suggest that the rise time is the better measure of the shell thickness, i.e., implosion dynamics, than say the FWHM.…”
Section: Long Pulse Saturn Experimental Resultsmentioning
confidence: 98%
“…In the last year or so, high wire number tungsten experiments on the Saturn facility operating in the 150-250 ns implosion time range have shown x-ray powers comparable to those in the short-pulse mode with corresponding power gains of four to seven. 14 Initial calculations and analytic modeling in Ref. 14 suggested that the initiation of the wire array may have been playing a key role in the achievement of the high quality implosions observed in the experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results from Saturn with aluminum wires, 6 Saturn with tungsten wires, 7,8 and Z with tungsten wires 9 are plotted in Fig. 2 with the full-width-half-maximum ͑FWHM͒ of the radiation pulse as a function of the interwire gap g w ϭ2R/N, where R is the initial array radius and N is the number of wires.…”
Section: Introductionmentioning
confidence: 99%